Implementation Of Food Security Policy In DKI Jakarta Province (A Case Study Of PT. Food Station Tjipinang Jaya) - Ahmad Ridwan Dalimunthe (Green Publisher Indonesia, 2024)
Food security is a strategic issue for densely populated areas like the Province of DKI Jakarta, which has limited agricultural land. This research aims to analyze the implementation of food security policies in DKI Jakarta, focusing on a case study of PT Food Station Tjipinang Jaya (FSJT) as the policy implementer. The study employs a qualitative approach using literature review methods, with data collected from various written sources such as regional regulations, official reports, scientific publications, and related websites. Through content analysis and data source triangulation, this research identifies FSJT's success in maintaining food availability, improving food access, strengthening the distribution system, and supporting local farmers. However, the implementation of the policy also faces challenges such as land limitations, food price fluctuations, changing dietary patterns, and program sustainability. Supporting data shows FSJT's contribution to the reduction of the poverty rate in DKI Jakarta from 11.5% (2021) to 10.56% (2022), as well as the distribution of 1.2 million tons of rice in 2022. Surveys also noted that 82% of the public were satisfied with FSJT's performance in maintaining food availability. To enhance food security in the future, recommendations include the development of vertical farming, strengthening community food resilience, nutritional education campaigns, and diversification of food sources. Ongoing efforts through these measures are essential to ensure the effective implementation of food security policies and the sustainability of development in the Province of DKI Jakarta.